Two-dimensional materials in electrocatalysis: a microscale investigation - Wu, Yao (Nanyang Technological University, 2024)
Electrocatalysts are essential for many renewable energy conversion processes. However, their performance is often limited by complex structures and reaction environments. Two-dimensional materials have emerged as promising candidates in electrocatalytic studies due to their unique physicochemical properties and versatility. Nonetheless, the microscale electrocatalytic behavior and mechanism of 2D materials remain inadequately understood. This thesis aims to investigate how the 2D structure of electrocatalysts influences their performance in various reactions, along with the underlying factors and processes involved. The primary approaches of this thesis are microscopic electrochemical tests, particularly on-chip ultra-microelectrode tests, and microscopic structural characterization, especially STEM. The first work focuses on transition metal oxides (TMOs) as OER electrocatalysts. High-quality Fe- and Co-based TMOs with reduced thickness are synthesized by CVD growth, thereby facilitating the electrocatalytic study with an ultra-microelectrode testing platform. The as-grown TMOs have a uniform (001) surface exposure, attributed to the template effect of the substrate, allowing for the measurement of the intrinsic OER performance on the (001) plane. The experimental results indicate that bimetallic CoFe2O4 exhibits higher OER activity than monometallic CoO and Fe3O4, with the activity showing an increasing trend as the thickness decreases. Moreover, microstructural characterization reveals that a five-atomic-thick reconstruction layer is formed on the surface of CoFe2O4 after the OER reaction, providing information for studying the stability of the catalyst. The second work delves into the role of 2D hBN as protective layers for electrocatalysts, building upon the findings of the first work that revealed the surface reconstruction. High-quality 2D hBN are prepared by a PVA-assisted exfoliation method, without defects and vacancies in the atomic scale. The micro electrocatalytic reaction is confined to Pt nano-electrocatalysts with hBN coverage, eliminating the interference of uncoated areas and defects in the protective layer. The results demonstrate that the hBN protective layer adeptly preserves the stability and activity of the Pt nano-electrocatalysts in acidic HER. The STEM analysis reveals the protection mechanism of the hBN layer, wherein it isolates the electrocatalyst nanoparticles from the harsh reaction environment and provides spatial confinement for them to mitigate aggregation. The third work examines the mechanism of electrocatalytic tunneling effect (ETE) using the microscopic electrochemical method. High-quality hBN, graphene, and mica with atomic thickness and large area are synthesized by a PVA-assisted exfoliation method. These three materials exhibit different electron and proton transport capabilities, facilitating the study of electron and proton related behavior. An ultra-microelectrode method is used for electrochemical testing, ensuring that only the areas covered by high-quality 2D layers participate in the reaction. The testing results underscore that, in acidic HER, 2D materials covered electrocatalysts predominantly follow a mass transport reaction pathway. Protons efficiently traverse the 2D layer to reach the metal surface, where the essential electrocatalytic reactions occur within the protective layer. This thesis demonstrates the effectiveness of combining microscopic electrochemical tests with microscopic structural characterization to investigate the impact of specific structures in 2D materials on electrocatalytic reactions and reveal their structural and compositional changes under varying reaction conditions. The results yield valuable insights into the intrinsic performance and properties of 2D materials as electrocatalysts or components in electrocatalytic systems, as well as the underlying mechanisms and influence factors. Moreover, this thesis also proposes potential directions for future research, such as optimizing the synthesis methods of 2D materials, exploring new architecture of 2D electrocatalysts, and developing new techniques for in situ or operando characterization. These avenues hold great promise in advancing the understanding and application of 2D materials in the realm of electrocatalysis.